Analisis Penerapan Balanced Scorecard Pada Kinerja Karyawan Bank BRI Unit Sokaraja Tengah - Julianti, Taliyah; Puspitaningrum, Devi; Hasna, Amelia Nilal; Shafrani, Yoiz Shofwa (Populer: Jurnal Penelitian Mahasiswa, 2025)
This study aims to explore the implementation of the Balanced Scorecard (BSC) through the digital system "MyCore" in measuring and improving employee performance at Bank BRI Unit Sokaraja Tengah. Using a descriptive qualitative approach, data were collected through semi-structured interviews with key informants, observations of work practices, and analysis of internal documents (performance reports, SOPs). Data analysis was carried out through data reduction, data presentation, and drawing conclusions with verification through source triangulation. The research findings indicate that the "MyCore" system integrates four BSC perspectives (finance, customer, internal business process, learning & growth) with specific performance indicators that affect incentives and career development. The financial and customer perspectives appear to have a strong emphasis, reflected in the direct impact on incentives and bonuses. The implementation of internal business processes is supported by standardization through MyCore and technology adoption. The importance of the learning and growth perspective is realized through regular training programs and bootcamp interventions for low-performing employees, which have proven effective in improving subsequent evaluation scores. In general, the implementation of the BSC via MyCore creates a structured, transparent, and adaptive assessment mechanism, encouraging productivity and professionalism. The implications of this study emphasize the importance of a transparent performance evaluation system that has a direct impact on career development and incentives, while also demonstrating the effectiveness of structured interventions in improving employee performance at the micro banking unit level.